The Mechanism for Anticancer and Apoptosis‐Inducing Properties of Cu(II) Complex with Quercetin and 1, 10‐Phenanthroline. Issue 38 (10th October 2022) - Done, Gulseven; Ari, Ferda; Akgun, Oguzhan; Akgun, Halime; Cevatemre, Buse; Gençkal, Hasene Mutlu
Abstract: This article covers the anticancer activities and mechanisms of action of Cu(II) complexes of flavonoid‐derived quercetin and 1, 10‐phenanthroline ligands. The antiproliferative activity of the complex and its ligands was evaluated by MTT, ATP, and SRB viability assays in human lung cancer cells (A549, H1299). Findings for apoptosis were determined by fluorescent staining, flow cytometry analysis, and the M30 antigen method. In addition, the mechanism of action of the complex was investigated by Annexin V staining, caspase 3/7 activity, ROS formation, and cell cycle analysis. The involvement of caspases, thus, apoptosis was confirmed by rescuing cell death by using a pan‐caspase inhibitor (Z‐VAD‐FMK). Again, increased ROS levels in the cell showed that death may occur by apoptosis. For this reason, the accuracy of ROS‐induced apoptosis in cells has been proven as a result of the application of N‐acetylcysteine (NAC), which is a ROS inhibitor. The efficacy of the complex was compared with Cisplatin and ligands. The results showed that the Cu(II) flavonoid complex is cytotoxic on lung cancer cells and may have the potential to act as an effective metal‐based anticancer drug with a lower IC50 over Cisplatin. Abstract : Cu(II) flavonoid complex showed stronger cytotoxic and apoptotic effects in A549 and H1299 lung cancer cells than Cisplatin and its ligands (quercetin and 1, 10‐phenanthroline). It was found that Cu(II) flavonoid complex induced apoptosis through activation of caspases, presence of Annexin‐V, ROS production and cell cycle arrest. @FerdaAr7